Videoclipe lachrimae - Souza, Ana Carolina Sá Martins de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This report presents the development stages of the Lachrimae music video narrative. The project features on the imagery field a free interpretation of Lachrimae instrumental music, in an audiovisual narrative construction that tries to translate music's emotion, with a production that assigns equal importance to the audible and visual plans in the message of video clip

O presente relatório apresenta as etapas de elaboração do videoclipe narrativo Lachrimae. O projeto apresenta no campo imagético uma interpretação livre da música instrumental Lachrimae, em uma construção narrativa audiovisual que tenta traduzir as emoções passadas pela música, com uma produção que atribui na mensagem do videoclipe a mesma importância aos planos sonoro e visual
Keywords: Vídeos musicais; Musica instrumental; Cinema; Music videos